Differences in short and long passes of midfield footballers - Bylbyl Sokoli; Gani Ibrahimi; Qendrim Jahaj (Kazimierz Wielki University, 2020)
Efficiency in the game of football is possible only if phenomena is systematically defined as it is of primary importance for structuring the basic movements and the technical-tactical elements in the game of football. The main purpose of this research is to compare the midfielders of Superleague and First League of Kosovo in the technical element of the pass which is very significant for the quality of a footballer and especially of a midfielder. To this end, three hypotheses have been put forward which have been partially realized. The obtained results show that the Kosovo Superleague midfielders have shown higher efficiency in these specific technical elements during the game: in total passes, in accurate passes, inaccurate passes, in accurate short passes where Superleague footballers have had fewer long incorrect passes.